Traditional Japanese formulas tokishakuyakusan and ogikenchuto suppress dermal sclerosis in bleomycin‐induced murine scleroderma. Issue 2 (October 2016) - Jeong, Seonjung; Kimura, Mari; Fujimoto, Makoto; Nogami, Tatsuya; Watari, Hidetoshi; Hikiami, Hiroaki; Shimada, Yutaka
ABSTRACT: Aim: Systemic scleroderma is a connective tissue disease of unknown etiology characterized by fibrosis of the skin and internal organs. There are few effective treatments for this disease. In this study, we examined the effectiveness of the traditional Japanese medicines keishibukuryogan (KBG), tokishakuyakusan (TSS), and ogikenchuto (OKT) in treating systemic scleroderma. Methods: Dermal sclerosis was induced in mice by daily injection of bleomycin. The mice were randomly divided into five groups based on treatment: KBG, TSS, and OKT groups (250 mg/kg/day), and two groups given water only (the sham and control groups). The sham group received local phosphate‐buffered saline injections (without bleomycin), and the control group received local bleomycin injections (without treatment). Kampo treatment groups also received local bleomycin injections. A daily dose of 0.01 mL of either kampo solution or water/g·bodyweight was given orally (through a stomach tube) for 4 weeks. Results: On histology at week 4, significantly fewer mast cells had infiltrated into the dermis in the TSS and OKT groups than in the control group; dermal sclerosis was also less severe in these groups. Furthermore, at week 1, the KBG, TSS, and OKT groups had significantly reduced serum transforming growth factor β1 (TGF‐β1). OKT and TSS had significantly reduced the level of malondialdehyde in the skin tissue. Conclusion: OKT and TSS suppressed the progression of dermal sclerosis by inhibiting mast cell infiltration, as well as by decreasing TGF‐β1 and oxidative stress.